Percutaneous Extraction of Transvenous Permanent Pacemaker/Defibrillator Leads—A Single-Center Experience - Murat Akcay; Serkan Yuksel (Medicina, 2024)
Background and Objectives: The number of cardiac pacemakers being used has increased in recent decades, and this increase has led to a rise in device-related complications, requiring percutaneous device extraction. Our aim was to present our single-center clinical experience in percutaneous lead extractions. Materials and Methods: We analyzed an observational retrospective cohort study of 93 patients for the transvenous removal of a total of 163 endocardial leads. We evaluated the device details, indications, lead characteristics, extraction methods, complications, reimplantation procedure, follow-up data, effectiveness, and safety. Results: Patients’ mean age was 68.6 ± 11.6 years. Lead extraction indications were pocket infection in 33 (35.5%), lead dysfunction in 33 (35.5%), and system upgrade in 21 (23%) cases, and lead endocarditis in 6 (6%) cases. The duration from implantation to extraction time was a detected median of 43 (24–87) months. The most common retracted lead type was the RV defibrillator lead (62%), and the lead fixation type was active for one hundred (61%) patients. A new device was inserted in 74 (80%) patients, and the device type was most commonly a CRT-D (61%). Patients were followed up at a median of 17 (8–36) months, and 18 patients (19%) died at follow-up. Complete procedural success was obtained in 78 (84%) patients, and clinical procedural success was obtained in 83 (89%) patients. Procedural failure was detected in 15 (16%) patients. Major and minor complications were detected in 10 (11%) and 6 (6.5%) patients, respectively. The most common minor complication was pocket hematoma. Conclusions: Our experience suggests that transvenous lead extraction has a high success rate with an acceptable risk of procedural complications. The simple manual traction method has a high rate of procedural success, despite a high dwell time of the lead.